Hubungan Interior Ruang Belajar dan Bermain Terhadap Perkembangan Sosial Emosional Anak Usia Dini - Dhea Shafira; Armanila Armanila; Indah Khoirunnisah Siregar (Journal of Early Childhood and Character Education, 2022)
In general, playing and learning activities in Kindergarten are carried out indoors, so that the interior elements of the room can affect children's activities which can be seen from their behavior while in the room. This behavior is also a manifestation of the social and emotional development of children. The interior of the study and play room is expected to play an effective role in realizing the educational goals of Kindergarten, in particular the social emotional development of children. This research was conducted with the aim of knowing the relationship between the interior of the study and play rooms on the socio-emotional development of early childhood at RA Mukhlisin. The method used in this research is quantitative research using data collection techniques. The results obtained from this study are that there is a relationship between interior design and early childhood development at RA Mukhlisin because in terms of play space, RA Mukhlisin has provided quite a lot of game tools with good and interesting conditions, so that children feel comfortable in playing. socialize or interact with friends